Recovery time and associated factors of severe acute malnutrition in children aged 0–59 months admitted to referral hospitals in Tanzania: an institution-based prospective cohort study - Samson, Anthony; Stephano, Elihuruma Eliufoo; Mugaya, Azaria; Mpembeni, Jackline Humphrey; Kessy, Eusebi; Ndunguru, Fredrick; Mahamba, Dina; Lumbe, Arnold Gideon; Mtoro, Mtoro J.; Ntwenya, Julius (Frontiers in Nutrition, 2025)
BackgroundMalnutrition represents a pervasive global health challenge that severely impacts individuals of all ages. In Tanzania, severe acute malnutrition (SAM) is a critical health issue, contributing substantially to morbidity and mortality among children under the age of five. In light of the scarcity of local research on this topic, the present study aimed to evaluate the recovery time from SAM and identify its predictors among children aged 0 to 59 months.MethodsThis hospital-based prospective cohort study enrolled 92 children aged 0–59 months with SAM who were admitted to two regional referral hospitals. Descriptive statistics were used to generate frequency distribution tables. A Cox proportional hazards regression model was used to identify factors associated with recovery time from SAM.ResultsThe recovery rate was 95.83%, with an average recovery time of 15 days. The predictors of recovery included children’s age, with those aged 25 to 55 months showing a tendency for quicker recovery (AHR = 1.1; 95%CI: 0.12–0.34; p = 0.001). Additionally, the children whose mothers or caregivers had university-level education were more likely to recover quickly (AHR = 1.56; 95%CI: 0.23–0.35; p = 0.003), indicating that the level of maternal or caregiver education positively influences the duration of recovery from SAM.ConclusionThe recovery rate and average recovery time observed in this study meet acceptable international standards. The factors associated with a higher likelihood of recovery included older child age and higher maternal or caregiver education levels. There is a greater need for targeted interventions at the community level to prevent SAM.